Circular RNAs in Eukaryotic Cells - Chen, Liang; Huang, Chuan; Wang, Xiaolin; Shan, Ge (Current genomics, 2015)
Circular RNAs (circRNAs) are now recognized as large species of transcripts in eukaryotic cells. From model organisms such as C. elegans, Drosophila, mice to human beings, thousands of circRNAs formed from back-splicing of exons have been identified. The known complexity of transcriptome has been greatly expanded upon the discovery of these RNAs. Studies about the biogenesis and physiological functions have yielded substantial knowledge for the circRNAs, and they are now more likely to be viewed as regulatory elements coded by the genome rather than unavoidable noise of gene expression. Certain human diseases may also relate to circRNAs. These circRNAs show diversifications in features such as sequence composition and cellular localization, and thus we propose that they may be divided into subtypes such as cytoplasmic circRNAs, nuclear circRNAs, and exon-intron circRNAs (EIciRNAs). Here we summarize and discuss knowns and unknowns for these RNAs, and we need to keep in mind that the whole field is still at the beginning of exciting explorations.